Miniaturized Bandpass Filters With Double-Folded Substrate Integrated Waveguide Resonators in LTCC - CHIEN, Hung-Yi; SHEN, Tze-Min; HUANG, Ting-Yi; WANG, Wei-Hsin; WU, Ruey-Beei (IEEE transactions on microwave theory and techniques, 2009)
This paper proposes miniaturized bandpass filters with double-folded substrate integrated waveguide (SIW) resonators using multilayer low-temperature co-fired ceramic (LTCC) technology. Formed by inserting a metal plate with two orthogonal slots into the cavity, the double-folded SIW resonator is used for the circuit size reduction with its footprint about a quarter of the conventional TE 101 mode. With LTCC technology, there is more flexibility to organize the cavities of filters because of the 3-D arrangement. The vertically stacked cavities are coupled by ldquoLrdquo- or ldquoUrdquo-shaped slots, and if arranged horizontally, by an inductive window on the common sidewall or a suspended stripline between the cavities. Through experimental measurements and simulations at both the Ka - V -bands, it has been demonstrated that the proposed filter has compact sizes and good frequency responses. The area of the fully stacked Chebyshev filter has 88% size reduction in comparison with a three-pole planar waveguide filter, while the vertically stacked quasi-elliptic filter has 74% size reduction in comparison with a four-pole planar waveguide filter.